بناء مقياس الذكاء الأخلاقي وفق مستويات الحكم الأخلاقي للطلبة الجامعيين - Al-Gagi, Raja; Al-Hidabi, Dawood Abdulmalek Yahya; Al-Hammadi, Abdullah (2018)

(untitled)
The study aims at developing a measurement tool of Moral Intelligence for university students based on Moral Judgment Levels. A Theoretical framework of Moral Intelligence based on Al-Ghazali philosophy of morals was developed. Then, a scale was designed and standardized. The study sample consist of 111 males and females biology student teachers at the faculty of education, Sana’a University, Yemen. The level of moral intelligence achieved by the sample was average.